Perfectionism and changes in athlete burnout over three months: Interactive effects of personal standards and evaluative concerns perfectionism - Madigan, D. J.; Stoeber, J.; Passfield, L. (Psychology of Sport and Exercise, 2016)
Objectives: A recent longitudinal study with junior athletes (Madigan, Stoeber, & Passfield, 2015) found perfectionism to predict changes in athlete burnout: evaluative concerns perfectionism predicted increases in burnout over a 3-month period, whereas personal standards perfectionism predicted decreases. The present study sought to expand on these findings by using the framework of the 2×2 model of perfectionism (Gaudreau & Thompson, 2010) to examine whether evaluative concerns perfectionism and personal standards perfectionism show interactions in predicting changes in athlete burnout. Design: Two-wave longitudinal design. Method: The present study examined self-reported evaluative concerns perfectionism, personal standards perfectionism, and athlete burnout in 111 athletes (mean age 24.8 years) over 3 months of active training. Results and conclusion: When moderated regression analyses were employed, interactive effects of evaluative concerns perfectionism×personal standards perfectionism were found indicating that personal standards perfectionism buffered the effects of evaluative concerns perfectionism on total burnout and physical/emotional exhaustion. To interpret these effects, the 2×2 model of perfectionism provides a useful theoretical framework.